2015
DOI: 10.1038/srep17217
|View full text |Cite|
|
Sign up to set email alerts
|

A new live-cell reporter strategy to simultaneously monitor mitochondrial biogenesis and morphology

Abstract: Changes in mitochondrial amount and shape are intimately linked to maintenance of cell homeostasis via adaptation of vital functions. Here, we developed a new live-cell reporter strategy to simultaneously monitor mitochondrial biogenesis and morphology. This was achieved by making a genetic reporter construct where a master regulator of mitochondrial biogenesis, nuclear respiratory factor 1 (NRF-1), controls expression of mitochondria targeted green fluorescent protein (mitoGFP). HeLa cells with the reporter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…We tested this using the live-cell reporter, NRF1mitoGFP, which contains an NRF1 binding sequence driving GFP protein expression fused with a mitochondrial localization signal. This allowed us to simultaneously monitor NRF1-mediated transcriptional activity as well as mitochondrial morphology (Hodneland Nilsson et al, 2015). As predicted from the NRF1 nuclear localization, we observed that moderate but chronic depletion of ATP induced NRF1-mediated transcription ( Fig.7D and S4D).…”
Section: Atp Depletion Activates Atm With Downstream Effects On Nrf1supporting
confidence: 66%
“…We tested this using the live-cell reporter, NRF1mitoGFP, which contains an NRF1 binding sequence driving GFP protein expression fused with a mitochondrial localization signal. This allowed us to simultaneously monitor NRF1-mediated transcriptional activity as well as mitochondrial morphology (Hodneland Nilsson et al, 2015). As predicted from the NRF1 nuclear localization, we observed that moderate but chronic depletion of ATP induced NRF1-mediated transcription ( Fig.7D and S4D).…”
Section: Atp Depletion Activates Atm With Downstream Effects On Nrf1supporting
confidence: 66%
“…Since MitoTracker-labeled MT can leak dye over time, control experiments were necessary to confirm the real uptake of MT. To overcome the limitation of dye fading in this case, the use of cells with a stable MT reporter [16] will allow improved monitoring of this phenomenon, including more precise quantitation of biodistribution and fate at longer time points. MT trafficking was found to be independent of pre-conditioning, proinflammatory, or anti-oxidant treatment of MSCs or mitogen stimulation of target PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, we could also evidence the natural transfer of MT in response to intraperitoneal infusion of MSCs in immune-competent mice. To overcome the limitation of dye fading in this case, the use of cells with a stable MT reporter [16] will allow improved monitoring of this phenomenon, including more precise quantitation of biodistribution and fate at longer time points.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, by culturing fibroblasts on micropatterned coverslips of various sizes, it was shown that mitochondrial network volume primarily depends on the size and shape of the cell (Chevrollier et al, 2012). Shape complexity of individual mitochondria can be described by several parameters, such as ‘solidity’ (compactness) (Westrate et al, 2014), ‘tortuosity’ (for twisted mitochondria) (Lihavainen et al, 2012) ‘Feret ratio’ (ratio between length and width, a descriptor of filamentous character) (Hodneland Nilsson et al, 2015), or Form Factor (a combined measure of mitochondrial length and degree of branching) (Koopman et al, 2008). Other morphological parameters, like the number of branches or branch intersections, give an estimation of shape complexity at the level of the mitochondrial network (Lihavainen et al, 2012; Nikolaisen et al, 2014; Westrate et al, 2014).…”
Section: Descriptions Of Mitochondrial Morphologymentioning
confidence: 99%